Investment banking in America : a history - Carosso, Vincent P. (Cambridge, Mass.: Harvard University Press, 1970)
The book analyze the changing role and practices of the investment banker in American economy from the 1890's to the1960's.
Includes index
Bibliography: p. [511]-541.
usc 22/05/2017
Loans
Keywords: Investment banking